Biparametric 3T Magentic Resonance Imaging for prostatic cancer detection in a biopsy-naïve patient population: a further improvement of PI-RADS v2?. Issue 12 (December 2016) - Stanzione, Arnaldo; Imbriaco, Massimo; Cocozza, Sirio; Fusco, Ferdinando; Rusconi, Giovanni; Nappi, Carmela; Mirone, Vincenzo; Mangiapia, Francesco; Brunetti, Arturo; Ragozzino, Alfonso; Longo, Nicola
Abstract: Objectives: To prospectively determine the diagnostic accuracy of a biparametric 3T magnetic resonance imaging protocol (BP-MRI) for prostatic cancer detection, compared to a multiparametric MRI protocol (MP-MRI), in a biopsy naïve patient population. Methods: Eighty-two untreated patients (mean age 65 ± 7.6 years) with clinical suspicion of prostate cancer and/or altered prostate-specific antigen (PSA) levels underwent a MP-MRI, including T2-weighted imaging, diffusion-weighted imaging (with the correspondent apparent diffusion coefficient maps) and dynamic contrast enhanced sequence, followed by prostate biopsy. Two radiologists reviewed both the BP-MRI and the MP-MRI protocols to establish a radiological diagnosis. Receiver operating characteristics curves were obtained to determine the diagnostic performance of the two protocols. Results: The mean PSA level was 8.8 ± 8.1 ng/ml. A total of 34 prostatic tumors were identified, with a Gleason score that ranged from 3 + 3 to 5 + 4. Of these 34 tumors, 29 were located within the peripheral zone and 5 in the transitional zone. BP-MRI and MP-MRI showed a similar performance in terms of overall diagnostic accuracy, with an area under the curve of 0.91 and 0.93, respectively ( p = n.s.). Conclusions: BP-MRI prostate protocol is feasible for prostatic cancer detection compared to a standard MP-MRI protocol, requiring a shorter acquisition and interpretation time, with comparable diagnostic accuracy to the conventional protocol, without the administration of gadolinium-based contrast agent.